Investigation of the new optical soliton solutions to the (2+1)-dimensional calogero-bogoyavlenskii schiff model - Sajawal Abbas Baloch; Muhammad Abbas; Muhammad Kashif Iqbal; Asnake Birhanu; M. R. Alharthi (Scientific Reports)
Abstract In this work, we use the ansatz transformation functions to investigate different analytical rational solutions by symbolic computation. For the (2+1)-dimensional Calogero-Bogoyavlenskii Schiff (CBS) model, we derive a variety of rational solutions, such as homoclinic breather solutions (HBs), M-shaped rational solutions (MSRs), periodic cross-rationals (PCRs), multi-wave solutions (MWs), and kink cross-rational solutions (KCRs). Their dynamic is shown in figures by selecting appropriate values for the pertinent parameters. The Calogero-Bogoyavlenskii-Schiff model describes the interface of Riemann waves in two spatial dimensions. The Riemann wave can be used to explain a wide range of physical phenomena, including internal ocean waves, tsunamis, tidal waves, and magneto-sound waves in plasmas.In addition, two different types of interactions between kink waves and M-shaped rational solutions are studied. The proposed model plays a crucial role in elucidating the internal structure of tangible composite phenomena in several fields such as nonlinear optics, wave behaviors in deep seas, plasma physics, and two-dimensional discrete electrical lattices. In order to verify the physical properties of the established solitons, we use constant parameter values to create 3D, 2D, and contour profiles of the solutions.